Mastery level of selected non-specialist public secondary home economics teachers - Aguila, Kristine Charis B.; De Guzman, Ines A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
The Home Economics teacher must thoroughly know the basics of the discipline, continually study the changes in society, and see the implications these changes have in the discipline in order to teach the subject in the proper context. This descriptive study determined the mastery level of selected Technology and Livelihood Education - Home Economics teachers and identified their methods for acquiring knowledge useful for teaching home economics in order to provide the basis for the type of intervention most appropriate for the selected teachers. Twenty three non-specialist public secondary home economics teachers were chosen as respondents using purposive sampling. An objective questionnaire was used to derive the respondents' Mastery Level of Knowledge on the following areas: Handicrafts, Clothing and Textiles, Foods and Food Services, Home Management Business, Family Health Care and Support Services, and Entrepreneurship. Results show that the respondents have an average Content Knowledge and Mastery Level in all the six areas. However, for the General Confidence Level, Entrepreneurship and Home Management Business have high certainty; above average in Foods and Food Service, Family Health Care, and Clothing and Textiles; and average in Handicrafts. A re-training of non-specialist TLE-Home Economics teachers that focuses on reconstructing misinformation and enhancing further their competencies is recommended so that they will be more prepared to teach home economics in the secondary curriculum.
Thesis Classification: P
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Home economics teachers -- Philippines